Association of depressive symptoms with sweat chloride variability and medication possession ratio during long-term Elexacaftor/Tezacaftor/Ivacaftor therapy in adolescents and young adults with cystic fibrosis - Michael Lorenz; Mariya Pavlova; Katja Erler; Anika Nader; Anne Moeser (Frontiers in Pediatrics, 2026)
Introduction Elexacaftor/tezacaftor/ivacaftor (ETI) sustainably improves lung function (FEV₁), quality of life and sweat chloride (SC) levels in people with cystic fibrosis (pwCF). Psychological comorbidities may impair treatment adherence. This study assessed ETI adherence using SC and medication possession ratio (MPR) and evaluated the impact of depressive symptoms. Methods In this retrospective observational study, 34 pwCF aged 12–21 years (median 17.3) initiating ETI between 2020 and 2022 were included. SC and FEV₁ were measured at baseline and annually over four years. Depressive symptoms were screened annually using the PHQ-9 (score ≥7). Adherence was assessed by MPR (1.0 = full medication supply). Patients with prior CFTR modulator therapy, insulin-dependent diabetes or organ transplantation were excluded. Results Fifteen pwCF (44.1%) screened positive for depressive symptoms (mean PHQ-9 scores 11 vs. 2). Median SC decreased significantly from 102.5 mmol/L (98–106.5) at baseline to 46.5 mmol/L (32.5–57.8) in year 1 ( p < 0.001) and remained stable thereafter. PwCF with depressive symptoms demonstrated greater SC variability during follow-up, with a trend toward higher SC levels at follow-up visit 4 (between-group p = 0.056), while the within-group increase from FV1 to FV4 was significant ( p = 0.012)., MPR declined significantly from 0.95 to 0.75 ( p < 0.05). FEV 1 improved significantly in year 1 compared to baseline (+11%, p < 0.001) and remained stable in both groups. Conclusion ETI leads to sustained improvements in lung function and sweat chloride in pwCF. A substantial proportion of patients screened positive for depressive symptoms, which was associated with increased long-term variability in sweat chloride and declining MPR but not lung function. Structured psychological monitoring and targeted interventions may be essential to support adherence and long-term treatment success.